176-02: A Novel In-Vitro Model to Study Flow Dynamics in the Human Right Heart. (10th June 2016) - Gulan, Utku; Saguner, Ardan; Akdis, Deniz; Brunckhorst, Corinna; Gotschy, Alexander; Binter, Christian; Holzner, Markus; Duru, Firat
Abstract: Purpose: In-vitro studies to better understand right ventricular (RV) flow dynamics are scarce. Thus, three-dimensional (3D) pulsatile flow in the RV was investigated with a novel in-vitro silicone model. Methods: A non-intrusive measurement technique, 3D Particle Tracking Velocimetry (PTV), has been applied to a silicone replica of the healthy human RV. The anatomic model is transparent, which allows optical access to the investigation domain (Fig.1, left). Pulsating flow conditions were analyzed in this compliant silicone model to assess the velocity field in detail, including mean kinetic energy (MKE) and the possible occurrence of disturbed flow. Results were compared with flow measurements in the same model using 3D cine phase-contrast magnetic resonance tomography. Summary of Results: Our results show highest kinetic energies at the RV outflow tract (5.8 ± 0.55 mJ) and subtricuspid region (3.2 ± 0.55 mJ) (Fig.1, right), well corresponding to typical predilection sites in patients with arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D). Spatially and temporally averaged MKE is 1.7 ± 0.55 mJ, which agrees with the in-vivo studies in literature. Conclusions: This novel silicone right heart model has the potential to help us understand the impact of flow dynamics and mechanical stresses on physiological adaptation in athletes and pathophysiological changes in RV diseases such as ARVC/D.